First detection of tetrodotoxin and high levels of paralytic shellfish poisoning toxins in shellfish from Sicily (Italy) by three different analytical methods. (January 2019) - Dell'Aversano, Carmela; Tartaglione, Luciana; Polito, Giuseppe; Dean, Karl; Giacobbe, Mariagrazia; Casabianca, Silvia; Capellacci, Samuela; Penna, Antonella; Turner, Andrew D.
Abstract: Paralytic shellfish toxins (PST) and tetrodotoxin (TTX) are naturally-occurring toxins that may contaminate the food chain, inducing similar neurological symptoms in humans. They are co-extracted under the same conditions and thus their combined detection is desirable. Whilst PST are regulated and officially monitored in Europe, more data on TTX occurrence in bivalves and gastropods are needed before meaningful regulations can be established. In this study, we used three separate analytical methods - pre-column oxidation with liquid chromatography and fluorescence detection, ultrahigh performance hydrophilic interaction liquid chromatography (HILIC) tandem mass spectrometry (MS/MS) and HILIC high resolution (HR) MS/MS - to investigate the presence of PST and TTX in seawater and shellfish (mussels, clams) collected in spring summer 2015 to 2017 in the Mediterranean Sea. Samples were collected at 10 sites in the Syracuse Bay (Sicily, Italy) in concomitance with a mixed bloom of Alexandrium minutum and A. pacificum . A very high PST contamination in mussels emerged, unprecedentedly found in Italy, with maximum total concentration of 10851 μg saxitoxin equivalents per kg of shellfish tissue measured in 2016. In addition, for the first time TTX was detected in Italy in most of the analysed samples in the range 0.8–6.4 μg TTX eq/kg. The recurring blooms of PST-producing species over the 3-year period, the high PST levels and the first finding of TTX in mussels from the Syracuse bay, suggest that monitoring programmes of PST and TTX in seafood should be activated in this geographical area. Highlights: Recurring blooms of Alexandrium minutum and Alexandrium pacificum in Syracuse bay. Toxin profile and content of seawater and shellfish collected in 2015, 2016, 2017. Paralytic shellfish toxins contaminating mussels at levels up to 10851 μg STX eq/Kg. First finding in Italy of tetrodotoxin in mussels at levels up to 6.4 μg TTX eq/Kg. Comparison among PreCOX-HPLC-FLD, UHPLC-HILIC-MS/MS, and HPLC-HILIC-HRMS for PST.